Influence of Regional Climatogeographic Conditions on The Distribution of Helmintoses in the Republic of Karakalpakstan (Texas Journal of Medical Science, 2022)
The article highlights the basic concepts of helminthiasis, the incidence rate of the population with various forms of helminthiasis and the dynamics of the incidence rate in the Republic of Karakalpakstan in 2014-2018